Training on Making Rat Empos Explosions, Application, and Introduction of Active Rat Holes in Binturu Village, Kelua District, Tabalong Regency, South Kalimantan - Muslimin Sepe; Helda Orbani Rosa; Noor Aidawati (Altifani Journal: International Journal of Community Engagement, 2023)
Rats are the main pests on rice plantations. The presence of rat pests in rice plantations begins at the time of vegetative age rice plants and peaks during the generative phase. The availability of feed sources in the form of rice grains that contain high carbohydrates causes rice planting to be inseparable from the presence of rat pests. Efforts to suppress rat pest populations around rice plantations are the first step in increasing production yields. Improper rat pest control will cause rats to bait strap. The nature of bait jerks by rats makes repeated use of rodenticides no longer effective. The utilization of rat empos explosions in active holes is expected to have a significant influence in suppressing rat pest populations in rice plantations. The results of community service show the enthusiastic attitude of farmer groups in Binturu Village, Kelua District, Tabalong Regency, South Kalimantan.